(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
The article lists the role and importance of digital pedagogy in ensuring the quality of higher education. The factors that have a positive effect on the quality and effectiveness of education are analyzed. The analysis of the features of using traditional and digital pedagogy in the educational process is described.